Sleep drive, not total sleep amount, increases seizure risk - Vishnu Anand Cuddapah; Cynthia T. Hsu; Fernanda Valle Sirias; Yongjun Li; Hrishit M. Shah; Christopher Saul; Samantha Killiany; Camilo Guevara; Joy Shon; Zhifeng Yue; Gabrielle L. Gionet; Mary E. Putt; et al. (Nature Communications)
Abstract Sleep loss has been associated with increased seizure risk since antiquity. Using automated video detection of spontaneous seizures in Drosophila epilepsy models, we show that seizures worsen only when sleep restriction raises homeostatic “sleep drive,” not simply when total sleep amount falls. This is supported by the paradoxical finding that acute activation of sleep-promoting circuits worsens seizures, because it increases sleep drive without changing sleep amount. Sleep-promoting circuits become hyperactive after sleep loss and are associated with increased whole-brain activity. During sleep restriction, optogenetic inhibition of sleep-promoting circuits to reduce sleep drive protects against seizures. Downregulation of the 5HT1A serotonin receptor in sleep-promoting cells mediates the effect of sleep drive on seizures, and we identify an FDA-approved 5HT1A agonist to mitigate seizures. Our findings demonstrate that while homeostatic sleep is needed to recoup lost sleep, sleep drive comes at the cost of increasing seizure susceptibility.